Tonight on the Titanic - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 1999)
The magic tree house transports Jack and Annie to the deck of the Titanic to find the mysterious gift that will free a small dog from a magic spell.
"A stepping stone book."
"RL: 2.2"--cover p. [4].
Keywords: Titanic (Steamship) -- Juvenile fiction; Titanic (Steamship) -- Fiction; Shipwrecks -- Fiction; Survival -- Fiction; Time travel -- Fiction; Magic -- Fiction